2021
DOI: 10.1186/s13195-021-00920-6
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-D-aspartate (NMDA) and cannabinoid CB2 receptors form functional complexes in cells of the central nervous system: insights into the therapeutic potential of neuronal and microglial NMDA receptors

Abstract: Background The cannabinoid CB2 receptor (CB2R), which is a target to afford neuroprotection, and N-methyl-D-aspartate (NMDA) ionotropic glutamate receptors, which are key in mediating excitatory neurotransmission, are expressed in both neurons and glia. As NMDA receptors are the target of current medication in Alzheimer’s disease patients and with the aim of finding neuromodulators of their actions that could provide benefits in dementia, we hypothesized that cannabinoids could modulate NMDA fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…At least part of this neuroprotection is modulated by activation of peripheral MO via CB2 during ischemia [237]. In addition, modulation of neuroinflammation is frequently suggested as the potential beneficial mechanism of the cannabinoid to alter the natural history of neurodegenerative diseases [238][239][240]. On the other hand, prolonged heavy use of cannabinoids results in hippocampal thinning, neuronal death, and various complications [241][242][243][244].…”
Section: Neurological Effects In the Context Of Cannabinoid Usementioning
confidence: 99%
See 1 more Smart Citation
“…At least part of this neuroprotection is modulated by activation of peripheral MO via CB2 during ischemia [237]. In addition, modulation of neuroinflammation is frequently suggested as the potential beneficial mechanism of the cannabinoid to alter the natural history of neurodegenerative diseases [238][239][240]. On the other hand, prolonged heavy use of cannabinoids results in hippocampal thinning, neuronal death, and various complications [241][242][243][244].…”
Section: Neurological Effects In the Context Of Cannabinoid Usementioning
confidence: 99%
“…However, it may be responsible for increased susceptibility to pulmonary infec-tion in recreational users and patients taking cannabinoid compounds for clinical conditions [90][91][92]325,333]. At the same time, antinociceptive and neuroprotective mechanisms are dependent on the anti-inflammatory action of cannabinoids [74,123,239,[334][335][336].…”
Section: Cytochromementioning
confidence: 99%
“…Whereas the D 1 is coupled to Gαs and D 2 to Gαi, the macromolecular complex formed when the two receptors are co-expressed in the same neuron couples to Gαq (Rashid et al, 2007; Hasbi et al, 2009;George et al, 2014;Perreault et al, 2015). Notwithstanding, conformational changes that affect the binding and signaling outputs produced by a given agonist have been shown in the interactions with the Gαi-coupled CB 1 R (Callén et al, 2012;Sierra et al, 2015;Angelats et al, 2018), the Gαscoupled adenosine A 2A receptor (Franco et al, 2019a), and the ionotropic NMDA receptor (Rivas-Santisteban et al, 2021). In one of the first studies of biased agonism in GPCR heteromers (CB 1 R/CB 2 R), Navarro and co-workers showed that the allosteric effect of CBD was particularly noteworthy for the endocannabinoid anandamide but also that the effect tested using different agonists was smaller in the heteromer (Navarro et al, 2018a).…”
Section: Different Macromolecular Environments Of the Cb 2 R Impact A...mentioning
confidence: 99%
“…In www.gpcr-hetnet.com and in Figure 2 interactions of CB 2 R with further GPCRs are not yet included (they have not yet been incorporated into the STRING database). Also missing are the recently described interactions of the CB 2 R with glutamate N-Methyl-D-Asp (NMDA) ionotropic receptors ( Rivas-Santisteban et al, 2021 ). From a therapeutic perspective, the fact that CB 2 R may interact with other receptors that are also targeted by cannabinoids, for instance with GPR18 and GPR55, is of high interest ( Balenga et al, 2014 ; Reyes-Resina et al, 2018 ; Martínez-Pinilla et al, 2019 ; Martínez-Pinilla et al, 2020 ; Rivas-Santisteban et al, 2021 ).…”
Section: Bidirectional Information Exchange Between Ligand and Cb ...mentioning
confidence: 99%
See 1 more Smart Citation